Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Atas - Nur Zaini (Fakultas Agama Islam Universitas Billfath, 2023)
The aim of this study is to analyze the implementation of the independent curriculum in learning Islamic Religion Education subject. Haw, the stages in implementing the independent curriculum in learning Islamic Religion Education at SMA 1 Simanjaya. Collecting data in this study using observation, interview, and documentation. The result of this study indicate that the implementation of the independent curriculum at SMA 1 Simanjaya was carried out with 4 stages; first, the deepened of the basic framework of the independent curriculum, where the Teacher of PAI at SMA 1 Simanjaya were actively involved in the workshop and make focus group discussion for preparation of TP, ATP and learning modules. Second, the stage of document preparation, there are the education Unit Operational Curriculum (KOSP), Learning Objectives (TP) and Learning Objectives Flow (ATP), Learning planning and assessment, and Planning projects to strengthen Pancasila student profiles (P5). For PAI subject matter, the PAI teacher team refers to the Formula E of Learning Outcomes. they determine a time allocation of 5 (five) study hours for PAI. Third. In the implementation stage of learning, PAI subjects consist of 5 elements presented with a regular approach with an allotted time of 5 hours per week. Forth, in the monitoring and evaluation phase, the teacher refers to the learning objectives and then compiles indicators of learning achievement based on the essential material.